Islamic Fintech as a Solution for the Development of Parallel Ijarah in Islamic Financial Institutions - Ulafa Fatma; Salwa Prameswari (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2025)
The digital world is increasingly vibrant in fostering business development and driving innovation across various sectors, including Islamic finance. Exploring the implementation of parallel ijarah contracts within Islamic Financial Institutions (IFIs) requires innovation to enhance financing surpluses in these institutions. Parallel ijarah is a leasing contract in which the leased object is re-leased. Essentially, ijarah is a contract that involves renting an asset such as vehicles, buildings, or even large machinery required for business purposes.Islamic fintech has emerged to offer digital-based financial services that can support business growth. This article employs qualitative research using a descriptive-analytical method. The discussion includes an explanation of the parallel ijarah scheme and its implementation within Islamic Financial Institutions. References are drawn from journals, books, fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), the Indonesian Civil Code (KUHPerdata), and the Compilation of Sharia Economic Law (KHES). Innovations in the parallel ijarah contract reveal potential through the use of Islamic fintech, applying technology to facilitate financing and relevant transactions. Development can be pursued by integrating Islamic fintech through platforms such as blockchain-based smart contracts and Peer-to-Peer (P2P) Lending systems, which can enhance efficiency, accountability, and monitoring of leased objects. This, in turn, minimizes risks and promotes wider adoption of the parallel ijarah contract.The presence of digital platforms also enables tracking of leased assets, ensuring that IFIs maintain the integrity of these assets, especially when the leased property is not owned by the institution itself. Concerns arise when such assets may be sold, damaged, or lost. The parallel ijarah contract serves as an innovative solution for Islamic financial institutions, offering lease-based financing without transferring asset ownership. This provides maximum benefit to clients with dynamic business needs, while also optimizing the strategic use of the parallel ijarah contract to enhance the competitiveness of IFIs and support the growth of the Islamic economy.